More cells, bigger cells or simply reorganization? Alternative mechanisms leading to changed internode architecture under contrasting stress regimes. Issue 1 (13th September 2013) - Huber, Heidrun; de, Jan; von, Eric J.; During, Heinjo J.; Anten, Niels P. R.
Summary Shading and mechanical stress (MS) modulate plant architecture by inducing different developmental pathways. Shading results in increased stem elongation, often reducing whole‐plant mechanical stability, while MS inhibits elongation, with a concomitant increase in stability. Here, we examined how these organ‐level responses are related to patterns and processes at the cellular level by exposing Impatiens capensis to shading and MS. Shading led to the production of narrower cells along the vertical axis. By contrast, MS led to the production of fewer, smaller and broader cells. These responses to treatments were largely in line with genetic differences found among plants from open and closed canopy sites. Shading‐ and MS‐induced plastic responses in cellular characteristics were negatively correlated: genotypes that were more responsive to shading were less responsive to MS and vice versa. This negative correlation, however, did not scale to mechanical and architectural traits. Our data show how environmental conditions elicit distinctly different associations between characteristics at the cellular level, plant morphology and biomechanics. The evolution of optimal response to different environmental cues may be limited by negative correlations of stress‐induced responses at the cellular level.